2017
DOI: 10.1016/j.molp.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Lamin-like Proteins Negatively Regulate Plant Immunity through NAC WITH TRANSMEMBRANE MOTIF1-LIKE9 and NONEXPRESSOR OF PR GENES1 in Arabidopsis thaliana

Abstract: Nuclear lamins are involved in multiple biological processes in metazoan cells. The proteins of the CROWDED NUCLEI (CRWN) family are considered lamin-like candidates in Arabidopsis, although the functions of these proteins are largely unknown. In this article we show that crwn1 crwn2 double mutant displays an enhanced resistance against virulent bacterial pathogens, and both virulent bacteria and salicylic acid (SA) induce transcription of CRWN1 gene as well as proteasome-mediated degradation of CRWN1 protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 78 publications
3
75
1
2
Order By: Relevance
“…Upon Pst DC3000 infection, they found no difference in linc1 and linc4 single mutants but enhanced resistance in linc1/2 and linc1/4 double mutants. Guo et al (2017) were able to observe lower SA levels in the linc1 linc2 double mutant than in wild-type plants after inoculation with Psm ES4326, whereas Choi et al (2019) found elevated SA levels only in linc1/2 double mutants. In the linc1/2 and linc1/4 double mutants, the same authors reported enhanced levels of cell death FIGURE 5 | LINC1 modulates the glucosinolate biosynthesis pathway.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Upon Pst DC3000 infection, they found no difference in linc1 and linc4 single mutants but enhanced resistance in linc1/2 and linc1/4 double mutants. Guo et al (2017) were able to observe lower SA levels in the linc1 linc2 double mutant than in wild-type plants after inoculation with Psm ES4326, whereas Choi et al (2019) found elevated SA levels only in linc1/2 double mutants. In the linc1/2 and linc1/4 double mutants, the same authors reported enhanced levels of cell death FIGURE 5 | LINC1 modulates the glucosinolate biosynthesis pathway.…”
Section: Discussionmentioning
confidence: 77%
“…The Arabidopsis genome contains four LINC genes which have been extensively documented regarding their roles in regulating nuclear structure, chromatin organization, and nuclear size (Dittmer et al, 2007;Sakamoto and Takagi, 2013;Wang et al, 2013;Guo and Fang, 2014;Grob et al, 2014). Recent work addressed the role of the LINC gene family in biological processes such as seed germination (Zhao et al, 2016) and plant immunity (Zhao et al, 2016;Guo et al, 2017;Choi et al, 2019). In the latter study, Guo et al reported that among the single and double linc mutant lines tested, they observed a slightly enhanced pathogen resistance phenotype in the single linc1-1 mutant against infection by the virulent Psm ES4326 pathogen, but a much FIGURE 4 | LINC1 modulates JA accumulation and signaling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations